2008
DOI: 10.1245/s10434-008-0237-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Receptor for Advanced Glycation End Products (RAGE) is Related to Prognosis in Patients with Esophageal Squamous Cell Carcinoma

Abstract: The receptor for advanced glycation end products (RAGE), known as a multiligand receptor for certain stress-associated factors, has been considered to affect the characteristic differences of various cancer cells. We analyzed the expression and clinicopathological significance of RAGE in esophageal squamous cell carcinoma. We investigated immunohistochemically the relationship between RAGE expression and clinicopathological factors, including prognosis, in surgical specimens of primary tumors in 216 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
3
22
0
1
Order By: Relevance
“…With regard to colorectal cancer, Kuniyasu et al [17] reported that RAGE was strongly expressed at the invasive front, and co-expression of RAGE and HMGB-1 was closely associated with invasion and metastasis. In contrast, RAGE expression is negatively associated with tumor progression in esophageal squamous cell carcinoma and nonesmall cell lung carcinoma [22,23]. These data suggest the organ-specific interaction of RAGE in tumor progression.…”
Section: Discussionmentioning
confidence: 78%
“…With regard to colorectal cancer, Kuniyasu et al [17] reported that RAGE was strongly expressed at the invasive front, and co-expression of RAGE and HMGB-1 was closely associated with invasion and metastasis. In contrast, RAGE expression is negatively associated with tumor progression in esophageal squamous cell carcinoma and nonesmall cell lung carcinoma [22,23]. These data suggest the organ-specific interaction of RAGE in tumor progression.…”
Section: Discussionmentioning
confidence: 78%
“…10 RAGE expression is negatively correlated with depth of invasion in esophageal squamous cell carcinoma, and tumors with positive RAGE expression exhibit better prognosis than those with negative RAGE expression. 11 Therefore, in order to expound the role of RAGE in gastric cancer, we investigated the expression of RAGE in human gastric cancer, and the effects of RAGE knockdown on biological behaviors of gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…5,20,27 RAGE is widely expressed in normal tissues, 12 and has been considered to affect the characteristic differences in various cancer cells. 21,25,27,35 Recent studies have shown that S100P-RAGE signaling plays a major role in tumor development. 5,6,17 Intrahepatic cholangiocarcinoma (ICC) shows the second most common primary liver cancer.…”
mentioning
confidence: 99%